The Effect Of Mudharabah, Musyarakah, Murabahah, And Qardh Financing To Profitability Of Sharia Commercial Banks In Indonesia Period 2015-2019: PENGARUH PEMBIAYAAN MUDHARABAH, MUSYARAKAH, MURABAHAH, DAN QARDH TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2015-2019 - Naura Mumtaz; Dewa Putra Kharisma Mahardika (Prodi Ekonomi Syariah Universitas Majalengka, 2021)
Islam is the largest religion in Indonesia. Therefore, nowadays sharia banks continue to grow every year. This is proven by the growing number of Sharia banks in Indonesia. Nowadays, Indonesian people are interested in sharia bank services. This is due to the existence of a non-usury system in sharia banks that is not owned by conventional banks. In conducting its business, the implementation of the sharia banking system is based on Islamic law (sharia). This study aims to determine the influence of Mudarabah, Musharakah, Murabaha, and Qardh Financing on the Profitability of Sharia Commercial Banks in Indonesia in 2015-2019 both simultaneously and partially. The data is obtained from the annual financial statements of each sharia commercial bank. The population used is sharia commercial banks in Indonesia for the period 2015-2019. Sampling was conducted on a nonprobability sampling by using purposive sampling. Obtained 45 samples from 9 Sharia Commercial Banks for 5 years. The analysis method uses data panel regression by Eviews software version 11. It is shown by the results that the financing of mudarabah, musharakah, murabaha, and qardh financing had a simultaneous effect on profitability. Mudarabah and Musharakah financing have no effect on profitability. Murabaha financing has negatively effects profitability and Qardh financing has positively effects profitability.